Volar Locking Plate for Distal Radius Fractures: Functional Outcomes and Complication Rates with a Minimum of One Year Follow-Up - G, Kastanis; A, Pantouvaki; P, Kapsetakis; M, Spyrantis; G, Magarakis; C, Christoforidis; I, Stavrakakis (International Journal of Innovative Research in Medical Science, 2021)
Distal radius fractures (DRF) are the most common type of fractures of the upper extremities with an incidence of 44% of all types of forearm and hand fractures. In unstable DRF, the aim of surgical treatment is to restore a functional wrist. Volar locking plate is supported in literature as a promising surgical method in treatment of these fractures. The aim of this study is to analyze the type and complication rate with applied volar locking plate, the percentage of revision surgery and the functional outcomes in a minimum of one year follow up. Material &Methods: 104 fractures in 98 patients with a mean range of 48,5 years-old age underwent for unstable distal radius fractures with volar locking plate. The main cause was simple fall to an outstretched hand. In ten cases the fracture was open while in 28 cases the DRF was accompanied with ulnar styloid. All fractures classified by AO/OTA in A2-3 27 cases, B1-3 in 45 and C1-3 in 32 cases. The majority of patients were operated within 48-72 hours after injury. In all cases an extended flexor carpi radialis approach was performed and a volar locking plate was applied in all DRF’s. In sixteen cases with base of ulnar styloid fractures, low profile locking plates were applied, while in the rest of patients Kirschner wires were used. Postoperatively all patients followed a standard protocol rehabilitation program with passive and active motion of fingers and wrist. Results: Patients were evaluated according to complication (type and rate), time to fracture union, range of motion, Visual analogue pain scale, Quick Dash Score and patients-rated wrist evaluation score. Complications were distinguished in major and minor. Patients under 60 years-old with type fracture A2-3 and B1-3 showed better range of motion and grip strength than patients over 65 years old. In cases with type fractures C1-3 and age over 65 years old, ROM and grip strength decreased compared with the unilateral side. The percentage of complication and reoperation appeared more increased in type C1-3 related to the other two types of fractures. Finally the mean Quick DASH was 11,1±12,8, RPWE was 9.8±13,6 and the range of motion was in extension 75,2±7,3, in flexion 74±8,9, in pronation 85,6±1,9, in supination 88,5±2,4 in radial deviation 9,8±1,2 and in ulnar deviation 41,1±4,6 and grip strength was an average of 84,7% of uninjured hand. Conclusion: Unstable fractures required operative treatment with volar locking plate to be the gold standard in recently years. Unfortunately VPL presents postoperative complications related with plate and screw position with comminuted fracture or soft tissue damage which cannot be ignored, and for these reasons may be inadequate for all types of distal radius fractures.